ATTITUDES TOWARDS THE POSITION OF ISRAEL REGARDING THE PROVISION OF AID TO DRUZE IN SYRIA DURING THE CIVIL WAR IN SYRIA - KHER-ALDEEN, Mahmood (Studia Universitatis Babes-Bolyai Studia Europaea, 2023)
This article examines the perceptions and attitudes towards the position of the State of Israel and Israeli Druze regarding the provision of aid to Druze in Syria during the civil war in Syria that took place between the years 2011 and 2017. The main goal of this article is to examine the perceptions and attitudes of senior officials in the Druze community and in Israel regarding the aid provided to Druze in Syria and its impact on the national and Druze identity among the Druze population in Israel.